119k views
4 votes
Simplify the following expression.

A.49
B.1/14
C.1/49
D.14

Simplify the following expression. A.49 B.1/14 C.1/49 D.14-example-1

2 Answers

0 votes

Answer:

C

Explanation:

Using the rules of exponents


a^(m) ×
a^(n)
a^((m+n))


a^(-m)
(1)/(a^(m) )

Hence


7^(-5/6-7/6) =
7^{-(12)/(6) } =
7^(-2), then


7^(-2) =
(1)/(7^(2) ) =
(1)/(49) → C

User Cappittall
by
5.7k points
4 votes

ANSWER

C. 1/49

EXPLANATION

The given expression is


{7}^{ - (5)/(6) } * {7}^{ - (7)/(6) }

Recall that:


{a}^(m) * {a}^(n) = {a}^(m + n)

We apply this product rule of exponents to get:


{7}^{ - (5)/(6) } * {7}^{ - (7)/(6) } = {7}^{ - (5)/(6) + - (7)/(6) }

This implies that:


{7}^{ - (5)/(6) } * {7}^{ - (7)/(6) } = {7}^{ - (12)/(6) }


{7}^{ - (5)/(6) } * {7}^{ - (7)/(6) } = {7}^( - 2)

Recall again that:


{a}^( - m) = \frac{1}{ {a}^(m) }

We apply this rule to get:


{7}^{ - (5)/(6) } * {7}^{ - (7)/(6) } = \frac{1}{ {7}^(2) }

This simplifies to:


{7}^{ - (5)/(6) } * {7}^{ - (7)/(6) } = (1)/(49)

User Orad
by
6.3k points